2019
DOI: 10.5811/westjem.2019.6.42657
|View full text |Cite
|
Sign up to set email alerts
|

Usability of Learning Moment: Features of an E-learning Tool That Maximize Adoption by Students

Abstract: Introduction: E-learning is widely used in medical education. To maximize the potential of E-learning tools, every effort should be made to encourage adoption by optimizing usability. We created Learning Moment (LM), a web-based application that integrates principles of asynchronous learning and learning portfolios into a platform on which students can document and share learning experiences that occur during clinical work. We sought to evaluate the usability of LM and identify features that optimize adoption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 27 publications
1
24
0
1
Order By: Relevance
“…Web-based learning is an accessible and effective learning method that educators and students use to supplement or replace traditional learning, especially during the outbreak of the COVID-19. In recent years, a large number of studies have reported that e-learning has been widely used in various disciplines, such as clinical medical education ( Aloia and Vaporciyan, 2019 ; Grabowski et al, 2020 ; Tretter et al, 2020 ), nursing education ( Sinclair et al, 2016 ; Voutilainen et al, 2017 ; Kim and Park, 2019 ), and higher education ( Chu et al, 2019 ; He and Yusop, 2020 ; Zhang et al, 2020 ). Therefore, the advantages of e-learning, such as flexibility in learning, convenience in enabling learners to review subjects, and more vivid and authentic displays of cases, are also recognized by educators and learners ( Fagö-Olsen et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Web-based learning is an accessible and effective learning method that educators and students use to supplement or replace traditional learning, especially during the outbreak of the COVID-19. In recent years, a large number of studies have reported that e-learning has been widely used in various disciplines, such as clinical medical education ( Aloia and Vaporciyan, 2019 ; Grabowski et al, 2020 ; Tretter et al, 2020 ), nursing education ( Sinclair et al, 2016 ; Voutilainen et al, 2017 ; Kim and Park, 2019 ), and higher education ( Chu et al, 2019 ; He and Yusop, 2020 ; Zhang et al, 2020 ). Therefore, the advantages of e-learning, such as flexibility in learning, convenience in enabling learners to review subjects, and more vivid and authentic displays of cases, are also recognized by educators and learners ( Fagö-Olsen et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Usability of these systems can vary ( 18 ), and excess time spent navigating the LMS can be a deterrent to use. Some educators have gone so far as to create their own LMS to meet learners’ needs of simplicity and usability ( 19 ).…”
Section: Tips For Completely Asynchronous Learningmentioning
confidence: 99%
“…The SUS is a 10‐item tool for the measurement of the usability of digital tools 15 . It is used extensively in multiple industries, including medical education, due to the reliability of results even with small sample sizes 16 . Surveys were voluntary, anonymous, and distributed electronically using Survey Monkey.…”
Section: Development Processmentioning
confidence: 99%
“…15 It is used extensively in multiple industries, including medical education, due to the reliability of results even with small sample sizes. 16 Surveys were voluntary, anonymous, and distributed electronically using Survey Monkey. Data were analyzed using descriptive statistics, and internal consistency of the SUS was analyzed using Cronbach's alpha.…”
Section: Development Processmentioning
confidence: 99%